2012
DOI: 10.1253/circj.cj-12-0468
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Accelerates Both Neointimal Coverage and Re-Endothelialization After Sirolimus-Eluting Stent Implantation in a Porcine Model

Abstract: Atorvastatin pretreatment can accelerate both neointimal coverage and re-endothelialization after SES implantation, which may be mediated by the mobilization of EPC and enhancement of the endothelial function of the neointima.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…Moreover, a favorable effect of statins on reendothelialization after DES implantation may influence the outcome. 20 According to recent pathological investigations, inflammation at stented sites was less severe in patients with newer DES than in those with first-generation DES, 4 and the lower CRP value in our patients with newer DES was compatible with that pathological finding. Recent use of biocompatible polymer and optimized drug dose contributes to these results of newer DES.…”
Section: Predictors Of Late-phase Crp Elevationsupporting
confidence: 77%
See 1 more Smart Citation
“…Moreover, a favorable effect of statins on reendothelialization after DES implantation may influence the outcome. 20 According to recent pathological investigations, inflammation at stented sites was less severe in patients with newer DES than in those with first-generation DES, 4 and the lower CRP value in our patients with newer DES was compatible with that pathological finding. Recent use of biocompatible polymer and optimized drug dose contributes to these results of newer DES.…”
Section: Predictors Of Late-phase Crp Elevationsupporting
confidence: 77%
“…The pleotropic anti‐inflammatory effects of statins could reduce late‐phase inflammation after DES implantation as previously reported and thus decrease MACE. Moreover, a favorable effect of statins on reendothelialization after DES implantation may influence the outcome …”
Section: Discussionmentioning
confidence: 99%
“…Walter et al 7 showed an accelerated rate of re-endothelization in simvastatintreated rats after balloon-induced ischemia, with concomitant increases in levels and adhesive properties of EPCs. Wang et al, 20 in a porcine model of PCI, found that atorvastatin pretreatment promotes neointimal coverage and reendothelization after sirolimus-eluting stent implantation, with a more pronounced EPC mobilization and improvement of endothelial function. The present study was specifically focused on the evaluation of statin efficacy in promoting EPC mobilization in the context of PCI patients.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this theory, a recent study using a porcine model with DES implantation showed that atorvastatin accelerated both neointimal proliferation and re-endothelialization after the DES through mobilization of EPCs and enhancement of neointima endothelial function [13]. It is evident that statins reduce atherosclerotic cardiovascular adverse events in a wide variety of patient populations through direct LDL-lowering effects.…”
Section: Roles Of Statins In Patients With Des Implantationmentioning
confidence: 95%